Online Dance Injury Monitoring: The Efficacy of Weekly Reporting and Respondent Compliance Over a 30-Week Period. Issue 2 (June 2023) - Dang, Yanan; Koutedakis, Yiannis; Chen, Ruoling; Wyon, Matthew
Background: Previous injury survey recall methods often use one-off questionnaires with varying periods of recall. These methods have proven to show injury incidence inaccuracies and limited information on injury etiology. Purpose: The present study aimed to examine the efficacy of a remote weekly self-report injury incidence and etiology tool. Methods: Two online questionnaires were developed based on the "Fit to Dance 2" survey and sent to volunteers. The first questionnaire was sent once and asked for complete injury history information. The second questionnaire was sent to each respondent on a weekly basis and it focused on new injuries and their causes and whether injuries that occurred in previous weeks were still affecting their dancing. The online survey was opened for full-time dance students from September 2020 to July 2021. All weekly data for each respondent were combined with a unique reference code using their account names, students' numbers, and schools' names. The proportion of participants who drop out is defined as the measurement of outcome. Results: A total of 756 respondents engaged in the survey from 16 different Chinese dance schools; the drop-out rate was 70.1%, with student respondents under 18 years old having a slightly lower drop-out rate than adult respondents (69%vs 71%). 33 respondents (4.4%) who completed all 30 weeks survey. These data allow other researchers to examine respondent compliance rates from a weekly survey. Conclusion: A reminder system and teacher engagement could potentially increase the response rate. For frequent completion questionnaires the design needs to be streamlined to increase compliance. It is concluded that the researchers would need to weigh reduced completion rates (<100%) against data efficacy to achieve generalizability.